Utilization of Ogura CMS germplasm with the clubroot resistance gene by fertility restoration and cytoplasm replacement in Brassica oleracea L. (1st May 2020) - Ren, Wenjing; Li, Zhiyuan; Han, Fengqing; Zhang, Bin; Li, Xing; Fang, Zhiyuan; Yang, Limei; Zhuang, Mu; Lv, Honghao; Liu, Yumei; Wang, Yong; Yu, Hailong; et al.
Abstract: Clubroot disease, a major plant root disease caused by Plasmodiophora brassicae, has become one of the most destructive diseases among cultivated cruciferous vegetables. However, clubroot-resistant Brassica oleracea materials are rare. A few clubroot-resistant cabbage varieties are available on the market, but all are Ogura cytoplasmic male sterile (CMS) types. Therefore, in this study, to reutilize the clubroot-resistant Ogura CMS germplasm of cabbage, a new fertility-restored Ogura CMS material, 16Q2-11, was used as a bridge to transfer the clubroot resistance (CR) gene from the Ogura CMS cytoplasm to the normal cytoplasm by a two-step method (a fertility restoration and cytoplasm replacement method). In the first cross for fertility restoration of Ogura CMS clubroot-resistant cabbage (FRCRC), 16Q2-11 was used as a restorer to cross with Ogura CMS materials containing the CR gene CRb2 . Eleven Rfo -positive progenies were generated, of which four contained CRb2 : F8-514, F8-620, F8-732 and F8-839. After inoculation with race 4 of P. brassicae, these four CRb2 -positive individuals showed resistance. Furthermore, F8-514 and F8-839 were then used as male parents in the second cross of FRCRC to cross with cabbage inbred lines, resulting in the successful introgression of the CRb2 gene into the inbred lines. All offspring produced from this step of cross, which had a normal cytoplasm, showed a high resistance to race 4 of P. brassicae and could be utilized for the breeding of clubroot-resistant cabbage varieties in the future. This is the first time that the Ogura CMS restorer has been used to restore the fertility of Ogura CMS clubroot-resistant cabbages, which could improve germplasm diversity in cabbage and provide a reference method for using CMS germplasm in Brassica crops.